Terapi Tertawa Mempengaruhi Penurunan Tekanan Darah pada Pasien Hipertensi - Clara Tasha Nabilah; Wa Ode Sri Asnaniar; Al Ihksan Agus (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Hypertension is a chronic condition characterized by high pressure in the arteries of the human body. As a result, the heart is forced to work more intensively to improve blood circulation in the body normally. This study aims to determine the effect of stress therapy on blood pressure in hypertensive patients in the working area of the Tamamaung Community Health Center, Makassar City. This study uses a quantitative research method with a quasy experimental research design by designing a two group pre-test post-test design. As for the sample calculation using the experimental formula that is obtained as many as 32 samples which will be divided each 16 respondents in the intervention group and the control group. Blood pressure was measured before laughing therapy was carried out and measured again after 3 times of therapy. Each group was given therapy 3 times for 7 days. The statistical test used is the paired sample t-test. The results of the paired sample t-test showed that there was a significant effect of reduced therapy on reducing blood pressure in the treatment group where systolic blood pressure and diastolic blood pressure after therapy p 0.000 < a 0.05. The conclusion of this study is that there is an effect of giving therapy which has an effect on reducing blood pressure in hypertensive patients in the working area of the Tamamaung Public Health Center, Makassar City.